Pengaruh Latihan Kekuatan Otot Lengan Terhadap Kemampuan Smash Dalam Permainan Bola Voli Pada Siswa SMAS Swadharma Mopugad - Jeanne R Malonda; I Wayan Sapta Sentana Putra; B.Sukadana (STIKES Columbia Asia Medan, 2024)
The formulation of the problem in this research is: What is the effect of arm muscle strength training on smash ability in volleyball games among SMAS Swadharma Mopugad students? The aim of the research is: To determine the effect of arm muscle strength training on smash ability in volleyball games among SMAS Swadharma Mopugad students. Research Hypothesis: There is an influence of arm muscle strength training on smash ability in volleyball games among SMAS Swadharma Mopugad students. The research method used is the experimental method. The population is all 20 class XI students at SMAS Swadharma Mopugad. Because the population in this study is small, the sample from this study is the entire population. Of the 20 students, they were divided into two groups, 10 people each in the experimental group and 10 people in the control group. The research design uses: Pre-Test and Post-Test with Randomized Groups. Hypothesis testing uses statistical techniques with the t test. The results of calculation analysis using t-test statistics obtained an observation t value of tob = 3.225. Meanwhile, from the table of critical values t with a real level of a = 0.05; n_1+n_2-2 obtained a t table value of ttab = 2.101. This fact shows that the value of tob = 3.225 > ttab = 2.101, thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted.